2015
DOI: 10.4028/www.scientific.net/amr.1119.569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alloying Elements and Impurity (N) on Bulk and Grain Boundary Cohesion in Cr-Base Alloys

Abstract: Effect of comprehensive alloying system (W, Ta, Nb, Mo, V, Hf, Ti, Zr, Ni) and impurity N on cohesive properties of the bulk and the special high-angle grain boundary (GB) Σ5 (210)[100] in Cr-base alloys, as well as segregation behavior of impurities at the GB and the (210) free surface are studied by first principles calculations. The analysis of the data obtained allows us to single out W, Ta as the best and nitrogen as the worst interatomic bond strengthening elements for both the bulk and GB in Cr-base all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In our previous study [16], we have shown that some of the "low alloying" elements that improve cohesive properties of Ni-base phase have a negative effect on the GB strengthening (η) of Cr-base phase (Zr, Hf, Nb, see line Cr-base). However, this fact is partly related to extremely high cohesive properties of Cr itself [17] and given that all of the selected alloying elements improve the bulk cohesion of Cr, alloying of our test alloy with Zr, Hf, Nb and Ta should not alter much the cohesive strength of the Cr-base phase.…”
Section: Computational Resultsmentioning
confidence: 99%
“…In our previous study [16], we have shown that some of the "low alloying" elements that improve cohesive properties of Ni-base phase have a negative effect on the GB strengthening (η) of Cr-base phase (Zr, Hf, Nb, see line Cr-base). However, this fact is partly related to extremely high cohesive properties of Cr itself [17] and given that all of the selected alloying elements improve the bulk cohesion of Cr, alloying of our test alloy with Zr, Hf, Nb and Ta should not alter much the cohesive strength of the Cr-base phase.…”
Section: Computational Resultsmentioning
confidence: 99%